Effect of post-harvest UV-C irradiation and calcium chloride on enzymatic activity and decay of tomato (Lycopersicon esculentum L.) fruit during storage - Saeideh Mansourbahmani; Behzad Ghareyazie; Sepideh Kalatejari; Reza Salehi Mohammadi; Vahid Zarinnia (Journal of Integrative Agriculture, 2017)
Tomato is one of the extensively consumed vegetable crops worldwide. The regular consumption of tomato decreases the incidence of chronic degenerative diseases such as certain types of cancer and cardiovascular diseases. The objective of this study was to find an appropriate method that not only reduces tomatoes decay, but also maintains its post-harvest quality. A factorial experiment based on randomized complete block design with three replications was conducted to evaluate effects of ultraviolet (UV)-C and CaCl2 applications on tomato during storage. The traits studied included ethylene, polygalacturonase (PG) activity, pectin methyl esterase (PME) activity, firmness, total phenol content, and fungal-induced decay were measured weekly during 35 days of storage. Both UV-C and CaCl2 treatments had positive effects on tomato quality as compared to control treatment. The 3 and 4.5 kJ m−2 levels of UV-C and 2% CaCl2 had positive effects on quality characteristics, respectivly. Fruits treated by UV-C and CaCl2 had higher phenol and firmness, and less PME activity, PG activity, ethylene production, and decay than the control fruits. In conclusion, increasing in storage duration significantly affected the fruits quality by increasing in ethylene, PME activity, PG activity, decay and decreasing the phenol content and firmness. But UV-C and CaCl2 led to significant decrease in this adverse impact relative to control treatment.